PLS discriminant analysis for classification of caries level / Katrul Nadia Basri ... [et al.] - Basri, Katrul Nadia; Mohd Zain, Mohd Norzaliman; Mohd Yusof, Zalhan; Zoolfakar, Ahmad Sabirin; Yazid, Farinawati (UiTM Press, 2024)
Saliva has been investigated as a possible diagnostic medium to detect the presence of dental caries. Salivary alpha-amylase has a direct connection with caries activity, making it a useful host-related factor biomarker. The saliva sample from UKM was used as a sample for the measurement of UV absorption spectroscopy. The UV spectra obtained shows the peak absorption around 280 nm that correlate with the amino acid in the salivary alpha amylase that works as a binding site of bacteria that responsible of caries. The spectra was split into calibration and validation for the development of the PLS model. Autoscale and MSC were used as data preprocessing for the model optimization. The best sensitivity and specifity acquired were 1.00 respectively with the AUC value of 1.00. Therefore, the UV absorption spectroscopy coupled with chemometrics can work as diagnostic tool for detection of dental caries.